Kehidupan ABK di Sekolah: Guru Menghadapi dan Memahami ABK - Mayda Yusnita; Elsa Hijriati; Nadia Nur'izzati; Opi Andriani (Institut Nalanda, 2024)
The aim of this research is to find out the lives of ABK at school and teachers dealing with and understanding ABK. This type of research is qualitative in nature with data collection mainly through books and journals as data sources. The data analysis technique is to use data triangulation. The research objects are books and journals about children with special needs. The research results concluded that autism is a type of ABK that influences children's lives